Empowering Bangladesh: A Study on Synergizing Renewable Energy and Smart Grid Technologies for Sustainable Development (IUBAT Review, 2024)
This paper shows a study of the Smart Grid in Bangladesh, emphasizing the incorporation of renewable energy sources. Its aim is to provide an overview of global renewable energy demand and highlight the significance of a smart grid system in fostering sustainability and dropping CO2 emissions.The total renewable energy generation of Bangladesh stood at a meager 1.34% in 2009, representing its low comparative position with other nations. Unfortunately, there has been a little improvement over time, as the total renewable energy generation was 1.51% in 2014 and only slightly increased to 1.57% by 2019. To overcome the addressed issue, it requires massive potential of renewable energy sources to ensure a lucrative, secure, and high-quality supply. This can be achieved through effective monitoring and control mechanisms within the grid system.The integration of cutting-edge technologies such as bi-directional current flow, bi-directional communication systems, automatic working capacity, automatic control systems, and rear systems are required if the upgradation of the current power structure is needed. These advancements will contribute to the enhanced performance, reliability, and security of the renewable energy infrastructure. By embracing a smart grid system and optimizing the integration of renewable energy, Bangladesh can pave the way towards a sustainable future. This will not only boost the country's renewable energy generation but also play a vital role in mitigating CO2 emissions.IUBAT Review—A Multidisciplinary Academic Journal, 7(1): 26-44